The conspiracy of life : meditations on Schelling and his time - Wirth, Jason M., 1963- (SUNY series in contemporary continental philosophy., 2003)
"The Conspiracy of Life offers a series of meditations on the philosophy of F.W.J. Schelling (1775-1854), a great - philosopher of life. Rather than construing him as a loopy mystic, or as an antiquated theologian, Jason M. Wirth attempts to locate Schelling as the belated contemporary of thinkers like Heidegger, Derrida, Bataille, Irigaray, Foucault, Deleuze, Levinas, and many others. As such, Schelling is already at the central nerve of current discussions concerning the crisis of truth; the primacy of the Good; the ecstatic nature of time; the nature of art; deep ecology; the world as an aesthetic phenomenon; comparative philosophy; the possibility of non-dialectical philosophy; radical evil; the haunting of philosophy; and the possibility of a philosophical religion."--Jacket